Comparative Analysis of Adam’s Repentance According to Islam and Judaism Perspectives - Nazmi Qayyum Hamdan; Muhammad Nasrullah Mohamad Azli (Rabbanica: Journal of Revealed Knowledge)
The Judaism and Islamic conceptions of repentance are nearly identical. The Quran and Torah mention the story of Adam and Eve eating the forbidden tree. Some Islamic scholars criticise the text of the Torah that exists today for the narrative style that portrays it as if Adam never repented of the act. Therefore, this research paper aims to identify Jewish scholars' position regarding Adam’s repentance. The first objective is to identify the recognition of Adam’s prophethood according to Islam and Judaism. The second objective is to identify the conviction of sin against Adam’s actions according to Islam and Judaism. According to Islam and Judaism, the third objective is to identify the certainty of Adam’s repentance. This research is a literary study, drawing information from the works of Islamic and Jewish scholars who have interpreted the story. A question was also asked to a contemporary Jewish scholar, Ben Abrahamson, who studies Islam. The results found that, first, Islam recognises Adam’s prophethood except for some contemporary scholars who deny it. However, for Judaism, it is not clearly stated that some Jewish scholars recognised Adam as a prophet. Second, Islam and Judaism admit that Adam sinned in that regard. Third, the Quran clearly says Adam repented, while the Torah does not. However, according to the oral tradition of Jewish scholars, Adam did repent through actions by immersing himself in the Gihon River for 130 years to atone for his sins.